Accuracy and effectiveness of orthophotos obtained from low cost UASs video imagery for traffic accident scenes documentation. (June 2019) - Pérez, Juan Antonio; Gonçalves, Gil Rito; Rangel, José Manuel Galván; Ortega, Pedro Fuentes
Highlights: A novel approach for documenting traffic accidents scenes is presented. Low cost video imagery and UAV photogrammetry are synergistic employed to generate an accurate orthophoto that is used for documenting the accident scene. The results obtained showed a horizontal accuracy in scene documentation ranging from 5 cm to 8 cm. Concerning the state-of-art of documenting traffic accident scenes, the proposed approach is very effective: simple, fast, low cost and accurate. Abstract: Mapping and documenting traffic accident scenes may vary from simple sketches and tape measurements to complex 3D measurements and modeling of the scene space which could involve expensive Terrestrial Laser Scanning instruments. In this paper we propose a novel approach for the documentation of traffic accidents scenes that is based on low-cost Unmanned Aerial Vehicle (UAV) technology and UAV photogrammetry methods. By using the onboard camera with a 4 K video recording feature, a very detailed and accurate orthophotos are generated from a set of the individual frames. Analyzing the orthophotos obtained from different case studies corresponding to different image overlaps and processing parameters, the horizontal accuracy in scene measurements ranged from 5 cm to 8 cm. This study also concludes that this state-of-art approach can be used effectively for traffic accidents scenes documentation.